PERSEPSI MASYARAKAT TERHADAP AKSESABILITAS PELAYANAN KESEHATAN - dewi, armoni suci; Suyanto, Suyanto; Sari, Dita Kartika (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2024)
The unequal availability of health facilities, health personnel and very varied geographic conditions, give rise to the potential for widening inequality in health utilization among communities in several regions in Indonesia. The gap in health services that exists between urban and rural areas contributes to an increase in the number of people suffering from chronic diseases in rural areas. This research aims to determine the community's perception of the accessibility of health services in Kepayang Kepuasan Hulu Village, District. Rokan Hulu.This type of research is descriptive qualitative and data sources are extracted from informants consisting of elements of society, community leaders and the public. Informants were selected using purposive sampling, data collection methods were carried out using FGDs and in-depth interviews. The results of informants had used health services at the health center,with the types of vehicles used mostly being private motorized vehicles, the costs incurred to access the health center were still considered affordable, but what was still an obstacle was the condition of the roads which were still dirt, where this condition would be more it is difficult to access when it is wet (after rain) and also the travel time is more than 1 hour, so it can be concluded that people's accessibility to the community health center is still hampered by road conditions. It is hoped that special attention will be paid to the condition of the road.